Expression of ANGPTL2 and its impact on papillary thyroid cancer - Longyan Yang; Rongxin Sun; Yan Wang; Ying Fu; Yuanyuan Zhang; Zhaohui Zheng; Zhili Ji; Dong Zhao (Cancer Cell International, 2019)
Abstract Background Although the most thyroid carcinoma patients have good prognosis, around 20% of papillary thyroid carcinoma (PTC) patients have a high rate of metastasis and recurrence after routine treatment, which causes high lethality with these patients. Tumor proliferation, metastasis, and invasion are important predictors of PTC invasiveness and are key factors in cancer-related death. Angiopoietin-like 2 (ANGPTL2), a secreted protein which belongs to the angiopoietin (ANGPTL) family, was reported to be involved in the regulation of several different type of cancer cell proliferation and metastasis. However, whether ANGPTL2 plays a role in the progression of PTC, particularly in metastasis and recurrence of PTC, remains unclear. Hence, the purpose of this study was to evaluate the level of ANGPTL2 in PTC and normal thyroid, as well as para-cancerous tissue. Furthermore, the impact of ANGPTL2 on PTC cell proliferation, metastasis, recurrence and invasion was assessed to investigate the possibility whether ANGPTL2 may become a novel target for PTC therapy and cancer prognosis. Materials and methods The level of ANGPTL2 in PTC and para-cancerous tissue was assessed by immunohistochemistry. The biological effect of ANGPTL2 on thyroid cancer cell proliferation and metastasis was investigated by the Cell Counting Kit-8 (CCK8) assay, cell scratch test, and transwell assay. Correlations of ANGPTL2 expression levels with proliferation, migration, and metastasis of thyroid cancer were assessed with the TCGA data set and analyzed by gene set enrichment analysis. Receiver operating characteristic analysis was used to evaluate the utility of ANGPTL2 as a biomarker for prediction of thyroid cancer. Survival analysis was performed using the thyroid cancer database in K–M Plotter to detect correlations between survival time and ANGPTL2 levels. Results Current study revealed that: (1) ANGPTL2 was highly expressed in thyroid cancer in comparison with adjacent normal thyroid tissue; (2) ANGPTL2 expression was increased with thyroid tumor progression; (3) ANGPTL2 increased proliferation of thyroid cancer cells; (4) ANGPTL2 promoted migration and invasion of thyroid cancer cells; (5) high level of ANGPTL2 in thyroid cancer patients were significantly associated with a poor prognosis. The patients showed a higher metastasis and recurrence rate. Conclusion ANGPTL2 promoted and enhanced proliferation, metastasis, and invasion of thyroid cancer cells. ANGPTL2 may be considered as a potential biomarker for diagnosis and prognosis of thyroid cancer patients. Further evaluation needs to be done to analyze the possibility of taking ANGPTL2 as a prognostic marker and therapeutic target for papillary thyroid cancer.